Analisa DRPs Kategori PCNE Pada Pasien Gagal Ginjal Akut Dengan Infeksi Tanpa Hemodialisis Di Rawat Inap RSUD Dr. Moewardi Surakarta - Indarto, Indarto; Novitasari, Meliana; Yulianto, Dwi Joko; Agustina, Dwi Tri; Sakka, La (LPPM Institut Pendidikan Nusantara Global, 2025)
Acute kidney injury (AKI) is a clinical condition caused by metabolic or pathological damage to the kidneys, characterized by a rapid and significant decline in kidney function along with elevated azotemia levels. This study aimed to analyze the occurrence of AKI due to the impact of drug therapy based on Drug Related Problems (DRPs) as categorized by the Pharmaceutical Care Network Europe (PCNE) in inpatients at Dr. Moewardi General Hospital in 2022. It also aimed to determine the effect of drug therapy on reducing leukocyte and urinary bacteria counts, as well as urea and creatinine levels in patients with infections not undergoing hemodialysis. This was a descriptive, non-experimental study using retrospective qualitative and quantitative methods. Quantitative data were analyzed using linear regression and paired sample t-test, while qualitative data were analyzed using the PCNE DRP classification. The study involved data from 10 patients diagnosed with AKI and infection without hemodialysis, with 18 DRP events identified. The analysis of drug therapy using the PCNE DRP framework showed an influence on kidney function, as several patients who were not initially diagnosed with AKI had elevated urea and creatinine levels upon examination, leading to an AKI diagnosis. However, the therapy given to these 10 patients was not optimal in addressing AKI. The analysis concluded that the drug therapy, although appropriate in its administration, did not significantly impact the reduction of leukocytes, urinary bacteria, or urea and creatinine levels, indicating that the therapeutic outcomes did not meet the expected results.